2001
DOI: 10.1111/j.0014-3820.2001.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Cytochrome C Genotypes Depends on Cytoplasmic Backgrounds in Tigriopus Californicus

Abstract: Because of their extensive functional interaction, mitochondrial DNA (mtDNA) and nuclear genes may evolve to form coadapted complexes within reproductively isolated populations. As a consequence of coadaptation, the fitness of particular nuclear alleles may depend on mtDNA genotype. Among populations of the copepod Tigriopus californicus, there are high levels of amino acid substitutions in both the mtDNA genes encoding subunits of cytochrome c oxidase (COX) and the nuclear gene encoding cytochrome c (CYC), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 43 publications
7
94
3
Order By: Relevance
“…This observation suggests that some NY two-locus genotypes may have had deleterious interactions with an additional Ec factor that was not linked to any segregating marker in our mapping population; such factors may have been absent either due to chance or, more likely, because they were maternally inherited cytoplasmic elements (Burke and Arnold 2001;Willett and Burton 2001;Levin 2003;Fishman and Willis 2006;Harrison and Burton 2006;Willett 2006;Chase 2007). This model implies that these genetic interactions involve multiple complementary loci, where the presence of a homospecific allele at either autosomal locus is sufficient for proper function.…”
Section: Discussionmentioning
confidence: 91%
“…This observation suggests that some NY two-locus genotypes may have had deleterious interactions with an additional Ec factor that was not linked to any segregating marker in our mapping population; such factors may have been absent either due to chance or, more likely, because they were maternally inherited cytoplasmic elements (Burke and Arnold 2001;Willett and Burton 2001;Levin 2003;Fishman and Willis 2006;Harrison and Burton 2006;Willett 2006;Chase 2007). This model implies that these genetic interactions involve multiple complementary loci, where the presence of a homospecific allele at either autosomal locus is sufficient for proper function.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, classic experiments demonstrated that simple genetic incompatibilities underlie hybrid inviability between Crepis species and cause the ''Corky'' syndrome of Gossypium species hybrids (Hollingshead 1930;Stephens1946). Similarly, in Tigriopus californicus, enzymatic activity of two interacting proteins, cytochrome c oxidase and cytochrome c, is reduced when they come from different populations (Rawson and Burton 2002), which might cause hybrid fitness problems (Willett and Burton 2001). In Xiphophorus, a simple two-locus incompatibility causes malignant tumor formation in species hybrids (Wittbrodt et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In angiosperms, hybrid male sterility is thought to result frequently from negative epistatic interactions between cytoplasmic (most probably mitochondrial) and nuclear genes in interspecific hybrids (Frank 1989;Schnable and Wise 1998). Negative cytonuclear interactions are also known to contribute to reproductive isolation between animal species and even populations, where they have been identified as the genetic basis of both hybrid inviability and infertility ½e.g., Tigriopus (Willett and Burton 2001;Harrison and Burton 2006) and Drosophila (Rand et al 2001;Sackton et al 2003). Assuming uniparental inheritance of the relevant organelle, cytonuclear interactions involve interactions between a cytoplasmic genome from one parent (usually maternal, Grun 1976) and the genes in the hybrid nuclear genome derived from the second parent.…”
Section: Classes Of Asymmetric Genetic Interactionsmentioning
confidence: 99%
“…generally differ in sterility in a small, and occasionally in a high degree,'' citing Kölreuter and Gärtner, the same plant hybridizers whose hundreds of intra-and interspecific crosses inspired Mendel in 1865 (translated in Bateson 1901). Asymmetry was subsequently found in essentially all systems subject to systematic hybridization experiments, including many invertebrates (e.g., Muller 1942;Oliver 1978;Harrison 1983;Coyne and Orr 1989a;Gallant and Fairbairn 1997;Presgraves and Orr 1998;Navajas et al 2000;Willett and Burton 2001;Presgraves 2002), vertebrates (e.g., Thornton 1955;Rakocinski 1984;Bolnick and Near 2005), and fungi (e.g., Dettman et al 2003). A recent analysis of reciprocal species crosses within 14 diverse angiosperm genera found significant isolation asymmetry in 35-45% of all species pairings, evaluated at three different postmating stages of reproductive isolation (Tiffin et al 2001).…”
mentioning
confidence: 99%